Evidence of improved shooting precision in biathlon after 10 weeks of combined relaxation and specific shooting training - Laaksonen, M. S.; Ainegren, M.; Lisspers, J. (Cognitive Behaviour Therapy, 2011)
The aim of this study was to test the hypothesis that a combined relaxation (applied tension release, ATR) and specific shooting training regimen may enhance shooting ability of biathlon athletes. Seven biathletes of high national level were randomized into an experimental group (age 20 ± 5 years; Vo2max 60 ± 8 mL kg(-1) min(-1)) and were asked to add this special training intervention to their regular training for 10 weeks, while five other biathletes served as controls (age 19 ± 2 years; Vo2max 57 ± 10 mL kg(-1) min(-1)). The shooting ability of the subjects was assessed before and after the intervention at rest and after roller skiing on a treadmill in a laboratory-based competition simulating assessment. After the intervention period, the experimental group demonstrated a significantly enhanced shooting performance compared to the control group. No changes in Vo2max or in heart rate and Vo2 responses were observed before and after the intervention in either group and there were no differences between the groups in these parameters. Thus, the preliminary conclusion is that a combination of ATR and specific shooting training seems to be instrumental in enhancing the shooting performance in biathlon.